Des lendemains incertains : immersion dans l’imaginaire du futur des adolescents. Étude sur l’intégration de la science-fiction et de la réalité virtuelle en enseignement des arts dans les écoles secondaires québécoises - Martin Lalonde; Géraldine Wuyckens (ReS Futurae, 2024)
This article presents the results of a research looking at the use of virtual reality (VR) in visual and media arts education in a project inviting teenagers to produce an anticipatory story about the world 1,000 years from now. Based on the interventionist methodology of design-based research in education, the Worlds of tomorrow project brings together researchers and field practitioners in education to create an immersive, interactive VR experience based on a science-fiction story produced by young people. This study aims to provide solutions to the problems of the lack of didactic resources for approaching VR and the lack of theoretical foundations to support teaching about and with science fiction in Quebec secondary schools. The article provides an account of how the project unfolded in the field, and then demonstrates how teenagers used the codes of videogame environments to create narratives that led their peers to experience empathic immersion. The results presented reveal that SF’s narrative processes, such as the novum, are relevant to help young people develop digital and media skills, and that the use of VR’s processes of immersion and interactivity enhanced SF’s educational capacities to elicit critique and contextualization of complex social issues and scientific and technological advances.